Central precocious puberty associated with duplicated pituitary: a case report and literature review - Yang, Kun; Sang, Yanmei; Dai, Li; Wang, Weizhong (Frontiers in Endocrinology, 2025)
Patients with duplicated pituitary often have severe neurodevelopmental abnormalities and craniofacial deformities. Till now, only eight patients diagnosed with duplicated pituitary showing barely central precocious puberty (CPP) are reported in the published literature. Herein, we report a 6-year-old and 3-month-old girl diagnosed with pituitary duplication presented with CPP. She has enlarged breasts for more than 1 year, accelerated height of linear growth, advanced bone age, increased hormone level, and increased volume of uterus and ovary. A duplicated pituitary gland was shown in the MRI. As the gonadotropin-releasing hormone analogue (GnRHa) stimulation test showed a positive result, the child was treated with GnRHa. After 2 years of follow-up, there was a delay in the progression of sexual development, a reduction in symptoms of precocious puberty, and an increase in predicted adult height.